Growth rate survival and preference of porina (Wiseana spp) to selected grasses - Atijegbe, S.R.; Mansfield, S.; Rost?s, M.; Worner, S.; Ferguson, C. (New Zealand Plant Protection, 2016)
Porina (Wiseana spp) has become a major pasture pest in New Zealand over the past century in response to natural forest and grasslands being converted into pastures for livestock Limited information is available on the growth and survival of porina larvae on native host species Field collected porina larvae were fed on 5 selected native plants (Festuca actae Aciphylla squarrosa Poa cita Chionochloa rubra and Phormium tenax) one exotic (Lolium multiflorum cv Manawa) and mixed species over 5 months and the fitness response of porina to each of these grasses was measured The most rapid growth of larvae was observed on L multiflorum while the slowest was on P tenax A squarrosa and P cita The largest weight gain was on L multiflorum There was a significant difference in larval growth between L multiflorum and P tenax (P0019) Percentage mortality was lowest on L multiflorum (125) with the larvae surviving for 177 days The highest mortality of 75 was recorded on P cita which also had the lowest survival of 77 days This study provided useful information on the development of porina on native hosts which provide a habitat for its expansion on to pasture